When Franny stands up - Robins, Eden, 1978- (Sourcebooks Landmark, 2022)
"Franny Steinberg knows there's powerful magic in laughter. She's witnessed it. With the men of Chicago off fighting WWII on distant shores, Franny has watched the women of the city taking charge of the war effort. But amidst the war bond sales and factory shifts, something surprising has emerged, something Franny could never have expected. A new marvel that has women flocking to comedy clubs across the nation: the Showstopper. When Franny steps into Chicago's Blue Moon comedy club, she realizes the power of a Showstopper-that specific magic sparked when an audience laughs so hard, they are momentarily transformed. And while each comedian's Showstopper is different, they all have one thing in common: they only work on women. After a traumatic flashback propels her onstage in a torn bridesmaid dress, Franny discovers her own Showstopper is something new. And suddenly she has the power to change everything...for herself, for her audience, and for the people who may need it most"--